Nutritional deficiency in South African adults scheduled for bariatric surgery - Sadhai, Prabash; Coetzee, Ankia; Conradie-Smit, Marli; Greyling, C. J.; van Gruting, Rutger; du Toit, Inge; Lubbe, Jeanne; van de Vyver, Mari; Conradie, Magda (Frontiers in Endocrinology, 2023)
Abstract Background Obesity is a rising trend globally and increases morbidity and mortality. Metabolic surgery and adequate weight loss decrease mortality but may worsen pre-existing nutrient deficiencies. Most data on pre-existing deficiencies in the population undergoing metabolic surgery is from the developed world, where an extensive micronutrient assessment is achievable. In resource-constrained environments, the cost of a comprehensive micronutrient assessment must be weighed against the prevalence of deficiencies and the risks if one or more deficiencies are missed. Methods This cross-sectional study investigated the prevalence of micronutrient and vitamin deficiencies in participants scheduled to undergo metabolic surgery in Cape Town, South Africa, a low-middle income country. We report on 154 participants who underwent a baseline evaluation from 12 July 2017 to 19 July 2020. We conducted laboratory measurements including vitamin B12 (Vit B12), 25-hydroxy vitamin D (25(OH)D), folate, parathyroid hormone (PTH), thyroid-stimulating hormone (TSH), thyroxine (T4), ferritin, glycated haemoglobin (HbA1c), magnesium, phosphate, albumin, iron, and calcium. Results Participants were predominantly female, aged 45 years (37-51), with a preoperative BMI of 50.4 kg/m2 (44.6-56.5). A total of 64 individuals had Type 2 diabetes mellitus (T2D), with 28 undiagnosed cases at study entry (18% of study population). 25(OH)D deficiency was most prevalent (57%), followed by iron deficiency (44%), and folate deficiency (18%). Other deficiencies (vitamin B12, calcium, magnesium, phosphate) were rarely encountered and affected 1% of participants. Folate and 25(OH)D deficiency were related to obesity classification, with a higher prevalence in participants with a BMI 40 kg/m2 (p <0.01). Conclusion We noted a higher prevalence of micronutrient deficiencies compared with data from similar populations in the developed world. The minimum baseline/preoperative nutrient evaluation in our population should include 25(OH)D, iron studies, and folate. Additionally, screening for T2D is recommended. Future efforts should seek to collate broader patient data on a national scale and include longitudinal surveillance after surgery. This may provide a more holistic picture of the relationship between obesity, metabolic surgery and micronutrient status inform more appropriate evidence-based care.